Relative age effect in Japanese male athletes - Nakata, H.; Sakamoto, K. (Perceptual and Motor Skills, 2011)
The present study investigated the relative age effect, a biased distribution of elite athletes` birthdates, in Japanese male athletes. Japan applies a unique annual-age grouping for sport and education, which is from April 1 to March 31 of the following year. A total of 4,318 male athletes was evaluated from 12 sports: baseball, soccer, basketball, volleyball, handball, golf, horse racing, rugby, American football, sumo, Ekiden (track and field in long distance), and badminton. They played in the top level of Japanese leagues for each sport in 2010. The distribution of the birth dates was examined in each sport and showed significant relative age effect in baseball, soccer, volleyball, Ekiden, basketball, sumo, and horse racing, but not in all sports. The findings suggest that although the school year in Japan starts on April 1, significant relative age effects are observed in some sporting events.